THE LEVEL OF STUDENTS SATISFACTION ON LEARNING ENGLISH FROM HOME AT MTI PASIA BOARDING SCHOOL DURING COVID-19 PANDEMIC - Yulmezi Yulmezi; Arifmiboy Arifmiboy (Acitya: Journal of Teaching and Education, 2021)
This research was motivated by the disruption of the student learning process during the Covid-19 pandemic at MTI PASIA. This research was conducted to know how the level of student satisfaction in class X, XI, and XII at MTI PASIA on learning from home using E-learning during the Covid-19 pandemic.The design of this research was survey and the instrument used is a questionnaire. The subjects of this research were students of class X, XI and XII with a total of 167 students and students who will be used as research samples as many as 118 students. The instrument validity test was carried out by distributing instruments to 3 experts as instrument validators and to analyze the data using quantitative descriptive techniques with percentages.Based on the results of research conducted by researchers, the title of this research is the level of satisfaction of students learning English from home at MTI PASIA during the COVID-19 pandemic. Researchers conducted research to know how the level of student satisfaction in learning English towards the objectives and learning components. The results obtained that the level of satisfaction of student towards learning objectives and learning component are 45.92%, teacher 48.30%, student 48.68%, material 50.78%, method 49.83%, strategy 48.89%, media 49.65% and evaluation 49, 48%. Theaverage answer was 48.94% or ≥40% -≤70% and that means they are quite satisfied, according to data interpretation that has been determined.